(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
We present a list of amphibians and reptiles collected during six field surveys in the municipalities of Tailândia, Tomé-Açu and Moju, region of the Belém area of endemism, eastern Amazonia, Brazil. We conducted surveys on several fragments of the Amazon rainforest located in a matrix of palm oil plantations (Elaeis guineensis) and/or old pastures recently removed for new plantations. A total of 108 species, including amphibians (50), turtles (3), crocodiles (2), amphisbaenians (3), lizards (22) and snakes (28) were identified. Our results show a phylogenetic pattern already known for the Amazon, with Hylidae and Leptodactylidae presenting higher species richness among amphibians, Gymnophthalmidae and Teiidae for lizards, and Dipsadidae and Colubridae among snakes. Despite the study areas being inserted within the "arc of deforestation" in northeastern Pará state, where fragmented forest can be found in a matrix of palm oil plantations, pastures and regenerating forests, it still harbors a high diversity of reptiles and amphibians. Large-scale, agribusiness palm oil plantations are expanding in the region, and actions are needed to minimize impacts on local fauna. For this, conservation efforts focused on the remaining fragments of forest are crucial to protect the high species diversity still found in the region.